Understanding Firms' Environmental Performance: Does News Matter? - Mamingi, Nlandu; Dasgupta, Susmita; Laplante, Benoit; Hong, Jong Ho (2012)
The empirical literature on environmental performance or compliance has followed two strands: one based on the impact of formal regulation as a means of inducing better environmental performance, and the other centered on the role of informal regulation that mainly emphasizes the role of communities and capital markets. In this report, we analyze the impact of environmental news in print media on firms' environmental performance. Using data from a survey of industrial facilities in the Republic of Korea, multivariate probit estimation results indicate that the publication of a firm's negative environmental news in print media and the firm's awareness of this publication may be as important predictors of a firm's environmental performance as other sources of pressure. This article thus reemphasizes the potentially important role of the public release of environmental information in influencing firms' environmental performance.